Return to Civilized Country: Islamic Religious Values and Collectivist Culture as Suppressors of Workplace Incivility in Indonesia - Gustiawan, Deni; Azzahra, Reynia Shifa (Jurnal Bisnis Mahasiswa, 2025)
This research focuses on workplace incivility in Indonesia, a country with collectivist cultural values and a Muslim majority. Using qualitative methods with in-depth interviews with employees in several companies in Indonesia, a collectivist country with a Muslim majority. The data obtained were analyzed to identify key themes related to perceptions and responses to workplace incivility. The results showed that collectivist cultural values and Islamic teachings have a significant influence on how employees respond to workplace incivility. Based on the perspective of collectivist values, employees tend to be more tolerant of mild workplace incivility behavior due to their desire to maintain harmony and avoid conflict. However, on the other hand, based on the perspective of Islamic religious values, more serious workplace incivility behavior that violates religious norms is more likely to be responded to with reprimands based on Islamic religious values. These findings provide practical implications for management in considering the cultural and religious context in responding to workplace incivility behavior. Training programs that emphasize the importance of collectivism and work ethic values based on Islamic religious values can help reduce incidents of workplace incivility and strengthen a harmonious work culture that is conducive to performance.